THE ROLE OF ARTIFICIAL INTELLIGENCE IN EDUCATION - Prof. Rafid Sabah al - Tamimi; Assistant Professor Dr. Sanaa Aluey Abdul Sada; Maryam Muzahem Abbas; Dr. Ismaiel Ogla Abdullateef (Scholars Digest Publishing, 2024)
Artificial intelligence is a broad field in computer science that deals with creating machines that can perform tasks that often require human intelligence, such as visual perception, speech recognition, decision-making, language translation, and more. AI systems can be designed to learn and adapt to new situations, making them ideal for solving complex problems that require human-like intelligence. AI has transformed various industries , including education, and is used to enhance teaching and learning experiences, and artificial intelligence has the potential to provide a wide range of benefits to education. One of the most important is the ability to personalize the learning experience for each student. Using artificial intelligence, teachers can analyze student performance data and preferences to create personalized lesson plans and assessments that match each student’s strengths and weaknesses. The current research examines the role of artificial intelligence in education in all its dimensions
Keywords: Artificial Intelligence, Education.